Analysis of Factors Affecting Muslim Traders (Case Study of Palakka Market Fruit Traders Bone District) - Agussalim Harrang; Asriati Asriati; Andi Rustam; Samsul Risal (ITB AAS INDONESIA Surakarta, 2020)
This study aims to determine the factors that affect the income of fruit traders in Palakka Market, Bone Regency. The population in this study was fruit traders in Palakka Market, Bone Regency, the number of samples in this study was 97 respondents. Sampling is used by using a system random sampling, the technique is a sampling technique where all individuals in the population. The results of data analysis research that is known states that trading capital, trading hours, and trading experience each have a significant effect on the income of traders. R Square value of 0.503 means that 50.3% of the factors affecting fruit traders' income can be explained by trading capital, trading hours and trading experience, while 49.7% is explained in other factors not examined in this study.